HUBUNGAN IMUNOGLOBULIN M (IGM) DAN IMUNOGLOBULIN G (IGG) DENGAN DERAJAT KEPARAHAN INFEKSI DENGUE DI RSUD DR. M. HAULUSSY DAN RS SUMBER HIDUP AMBON PERIODE 2018 - Putri Ulandari; Vina Z. Latuconsina; Halidah Rahawarin (Fakultas Kedokteran Universitas Pattimura, 2020)
The dengue virus that has been injected through the bite of the Aedes mosquito will spread through the blood and cause primary viremia. This situation will stimulate the body's immune system to eliminate dengue infection, including the secretion of immunoglobulin M (IgM) and immunoglobulin G (IgG). Different immune system mechanisms will have an impact on the severity of dengue infection. This study aims to determine the relationship between IgM and IgG with the severity of dengue infection patients in RSUD. Dr. M. Haulussy and RS. Sumber Hidup Ambon in 2018. This research is an analytic cross-sectional approach that uses secondary data. The number of samples was 26 patients with purposive sampling. The result showed primary infections were at mild severity, while the secondary infection was found all severity. The analytic concluded there is no relation between IgM and IgG with the severity of dengue infection (p=0,237).